The Influence of Science Learning on Problem-Solving Skills of Early Childhood at Cahaya Generasi Bangsa Early Childhood Education Center Pontianak - Anjelina, Anjelina; Sudarti, Sudarti; Yuniarti , Yuniarti (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2025)
This study aims to examine the effect of science learning on the problem-solving abilities of early childhood students. The research was conducted at PAUD Cahaya Generasi Bangsa in Pontianak, where preliminary observations indicated that approximately 50% of children required assistance when engaging in problem-solving activities during science lessons, such as the volcano experiment. This finding highlights the need for a more structured and engaging science learning approach to support cognitive development in young learners. The study employed a quantitative approach with a one-group pretest-posttest design, involving a sample of 25 children. Data collection techniques included observation, problem-solving tests, and documentation of children’s activities. The data were analyzed using the Paired Sample T-Test to determine the significance of changes in problem-solving abilities before and after the implementation of science-based learning interventions. The results revealed a significant improvement in children's problem-solving skills after participating in science learning activities, indicated by a Sig. (2-tailed) value of 0.001, which is less than the significance threshold of 0.05. The average score increased substantially from 4.8 in the pretest to 13.36 in the posttest. Based on these findings, it is recommended that science learning be consistently integrated into early childhood education curricula to foster critical thinking, creativity, and independent problem-solving in young children.